Detection and genetic characterization of porcine deltacoronavirus in Tibetan pigs surrounding the Qinghai-Tibet Plateau of China - Wang, M; Wang, Y; Baloch, A R; Pan, Y; Tian, L; Xu, F; Shivaramu, S; Chen, S; Zeng, Q (Transboundary and emerging diseases, 2018)
Porcine deltacoronavirus (PDCoV) is a recently discovered RNA virus that belongs to the family Coronaviridae and genus Deltacoronavirus. This virus causes enteric disease in piglets that is characterized by enteritis and diarrhoea. In our present investigation, 189 diarrhoeic samples were collected between July 2016 and May 2017 from Tibetan pigs inhabiting in three different provinces surrounding the Qinghai-Tibet Plateau of China. We then applied the molecular-based method of reverse transcription polymerase chain reactions (RT-PCRs) to detect the presence of PDCoV in collected samples, and RT-PCR indicated that the prevalence of PDCoV was 3.70% (7/189) in Tibetan pigs. Four of 7 PDCoV-positive pigs were monoinfections of PDCoV, three samples were co-infections of PDCoV with porcine epidemic diarrhoea virus (PEDV), and 52 (27.51%) samples were positive for PEDV. Four strains with different full-length genomes were identified (CHN/GS/2016/1, CHN/GS/2016/2, CHN/GS-/2017/1 and CHN/QH/2017/1), and their genomes were used to analyse the characteristics of PDCoV currently prevalent in Tibetan pigs. We found a 3-nt insertion in the spike gene in four strains in Tibetan pigs. Phylogenetic analysis of the complete genome and spike and nucleocapsid gene sequences revealed that these strains shared ancestors with the strain CHN-AH-2004, which was found in pigs from the Anhui province of China mainland. However, PDCoV strains from Tibetan pigs formed different branches within the same cluster, implying continuous evolution in the field. Our present findings highlight the importance of epidemiologic surveillance to limit the spread of PDCoV in livestock at high altitudes in China.
Keywords: průjem; feces; Tibetan pigs; Coronavirus; Phylogeny; koronavirové infekce; Sequence Analysis, DNA; prevalence; Viral Proteins; genom virový; Swine Diseases; Diarrhea; Coronavirus Infections; China; kvantitativní polymerázová řetězová reakce; zvířata; Swine; Feces; sekvenční analýza DNA; Qinghai-Tibet Plateau; virové proteiny; Genome, Viral; porcine deltacoronavirus; fylogeneze; nemoci prasat; Real-Time Polymerase Chain Reaction; Tibet; Prevalence; Animals; prasata